1998
DOI: 10.2190/dqnq-pfam-7v00-52f3
|View full text |Cite
|
Sign up to set email alerts
|

Bereavement and Stress of a Miscarriage: As it Affects the Couple

Abstract: Perinatal death affects nearly one-third of all pregnant women (Toedter, Lasker, & Alhadeff, 1988). Of the different forms of perinatal death, this study explored the psychological impact of grief and stress in couples who experienced a miscarriage. Using the Grief Experience Inventory—Loss Version and The Impact of Event Scale, this study specifically looked at the differences between the couple in how they grieve and experience the stress of the miscarriage. Profile analyses indicated that the women's ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 19 publications
1
45
0
Order By: Relevance
“…Prior researchers note an increase in marital tension following the loss of a child that is related to gender differences in grieving patterns between partners (Alderman, Chisholm, Denmark, & Seibold, 1998;Littlewood, Cramer, Hoekstra, & Humphrey, 1991;Schwab, 1992). Incongruent grief can cause strain on a marriage as each spouse deals with loss in his or her own way (de Montigny, Beaudet, & Dumas, 1999;Puddifoot & Johnson, 1999).…”
Section: Conceptualizing the Link Between Loss And Divorcementioning
confidence: 99%
“…Prior researchers note an increase in marital tension following the loss of a child that is related to gender differences in grieving patterns between partners (Alderman, Chisholm, Denmark, & Seibold, 1998;Littlewood, Cramer, Hoekstra, & Humphrey, 1991;Schwab, 1992). Incongruent grief can cause strain on a marriage as each spouse deals with loss in his or her own way (de Montigny, Beaudet, & Dumas, 1999;Puddifoot & Johnson, 1999).…”
Section: Conceptualizing the Link Between Loss And Divorcementioning
confidence: 99%
“…Although a variety of standardized grief assessment instruments were used, along with widely different sample sizes and assessment intervals, men were found to experience significantly less intense levels of grief for a shorter period following a miscarriage than women in eight of the eleven studies that could be located. [57][58][59][60][61][62][63][64] Of the three studies that produced somewhat contradictory results, two used only a male cohort and compared scores on the PGF with norms for women. Men's and women's scores were found to be comparable following miscarriage.…”
Section: Gender and Intensity Of Grief Following Miscarriagementioning
confidence: 99%
“…She may be scared by the pain she suffers and by the blood she sees and this makes her very sensitive to every word and gesture from the staff. To the health care professionals the woman with a miscarriage may be regarded as a simple routine case (Alderman, Chisholm, Denmark, & Salbod, 1998;Cecil, 1994;Griffin, 1998;Moulder, 1999;Nielsen, Hahlin, & Platz-Christensen, 1999). Most women experience an intense period of emotional distress immediately following the loss, characterized by grief, dysphoria, guilt, and anxiety (Friedman & Gath, 1989;Lepppert & Pahlka, 1984).…”
mentioning
confidence: 99%
“…Most women experience an intense period of emotional distress immediately following the loss, characterized by grief, dysphoria, guilt, and anxiety (Friedman & Gath, 1989;Lepppert & Pahlka, 1984). Various feelings experienced include despair, anger, social isolation, rumination, somatization, and death anxiety (Alderman et al, 1998). One study of 65 women who had a spontaneous abortion found that 88% felt sad immediately after the miscarriage.…”
mentioning
confidence: 99%